Politik Hukum Terhadap Sistem Hukum Negara Kesatuan Republik Indonesia Dalam Menjamin Kepastian Hukum - Ni Ketut Tri Srilaksmi (IAHN Tampung Penyang Palangka Raya, 2022)
Politics cannot be separated from human action itself. In the legal system in Indonesia itself, politics is the main space in running the wheels of government and the government system. The Third Amendment to the Constitution of the Unitary State of the Republic of Indonesia in Chapter I Article 1 paragraph (3), reaffirms that